A guide to ethics and public policy finding our way - Welch, Don (Routledge, 2014)
Developed by D. Don Welch during his twenty-eight years of teaching ethics and public policy, the rationale behind A Guide present specific cases that raise moral issues or discuss the role a few concepts play in the moral analysis of policy, this book instead provides a broad framework for the moral evaluation of public policies and policy proposals. This framework is organized around guiding five principles: benefit, effectiveness, fairness, fidelity, and legitimacy. These principles identify the factors that should be taken into account and the issues that should be addressed as citizens address the question of what the United States government should be able to do. Organized by concept, with illustrations and examples frequently interspersed, the book covers both theory and specific issues. A Guide to Ethics and Public Policy outlines a comprehensive ethical framework, provides content to the meaning of the five principles that comprise that framework through the use of illustrations and examples, and offers guidance about how to navigate one's way through the conflicts and dilemmas that inevitably result from a serious effort to analyze policies